Modelling the Growth of Moraxella sp. B on Monobromoacetic acid (MBA) (Bulletin of Environmental Science and Sustainable Management (e-ISSN 2716-5353), 2015)
Monohalogenated acetic acids have been widely used in industry and agriculture as precursor tochemicals and as herbicides, respectively. Bioremediation of xenobiotics have been touted as amore economical and feasible method compared to physical and chemical approaches. In thiswork, we model the growth of Moraxella sp. B on monobromoacetic acid (MBA) from publishedliterature to obtain vital growth constants. These growth constants can only be accuratelyobtained from mathematical modelling of the growth curves using various available primarymodels such as logistic, Gompertz, Richards, Schnute, Baranyi-Roberts, Von Bertalanffy,Buchanan three-phase and more recently Huang models. The Buchanan three-phase model waschosen as the best model based on statistical tests such as root-mean-square error (RMSE),adjusted coefficient of determination (R2), bias factor (BF), accuracy factor (AF) and correctedAICc (Akaike Information Criterion). The constants obtained indicated that the lag period wasincreased as the concentrations of MAB was increased. In addition, the growth rate was severely reduced at high concentrations of MAB indicating substrate inhibition. Novel constants obtained from the modelling exercise would be useful for further secondary modelling implicating the effect of media conditions and other factors on the growth of this bacterium on MAB.
Keywords: growth curve, mathematical model, monobromoacetic-degrading, Buchanan-three-phase, statistical analysis